2003
DOI: 10.2298/hel0338039p
|View full text |Cite
|
Sign up to set email alerts
|

Androgenetic response of sunflower indifferent culture environments

Abstract: Production of microspore-derived embryos from cultured anthers is now a well-established technique for the isolation of homozygous lines in sunflower. Experiment was conducted to optimize the culture composition for wild Helianthus and inerspecific hybrids. Anthers of uninucleate microspores were cultured in basal MS media with different hormonal combinations. The induction of callus was quick and proliferation high with the presence of 2,4-D, low cytokinin and auxin contents. Excess cytokinin and auxin had no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(16 citation statements)
references
References 12 publications
0
15
0
1
Order By: Relevance
“…The doubled haploids of sunflower can be produced in vitro from an anther culture by direct embryogenesis [ 9 , 17 , 38 , 39 ], indirect embryogenesis [ 13 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ], or indirect shoot organogenesis [ 10 , 17 , 38 , 40 , 44 , 47 , 48 , 49 , 50 , 51 , 52 ] ( Figure 1 ). Several independent research groups have reported the formation of callus tissue from anther culture without any subsequent morphogenic response ( Table 1 and Table 2 ) [ 9 , 17 , 30 , 41 , 42 , 43 , 44 , 47 , 48 , 49 , 50 , 53 ].…”
Section: Production Of Sunflower Haploids In Isolated Anther Culturesmentioning
confidence: 99%
See 4 more Smart Citations
“…The doubled haploids of sunflower can be produced in vitro from an anther culture by direct embryogenesis [ 9 , 17 , 38 , 39 ], indirect embryogenesis [ 13 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ], or indirect shoot organogenesis [ 10 , 17 , 38 , 40 , 44 , 47 , 48 , 49 , 50 , 51 , 52 ] ( Figure 1 ). Several independent research groups have reported the formation of callus tissue from anther culture without any subsequent morphogenic response ( Table 1 and Table 2 ) [ 9 , 17 , 30 , 41 , 42 , 43 , 44 , 47 , 48 , 49 , 50 , 53 ].…”
Section: Production Of Sunflower Haploids In Isolated Anther Culturesmentioning
confidence: 99%
“…The time interval from the beginning of anther culture to callus tissue formation and the subsequent organogenesis or embryogenesis varies considerably. In particular, callus is formed in vitro on days 5–10, depending on the genotype [ 40 , 42 , 51 ], on days 10–15 [ 45 , 54 ], on days 15–20 [ 14 , 52 ], and after 4 weeks of cultivation [ 41 , 44 ]. Indirect shoot organogenesis or embryogenesis is observable after 4 weeks of culture [ 10 ] and later, after 80–100 days [ 52 ] or 120 days [ 51 ].…”
Section: Production Of Sunflower Haploids In Isolated Anther Culturesmentioning
confidence: 99%
See 3 more Smart Citations